Factors Associated with Anaemia among Pregnant Women in Indonesia : A Systematic Review - Widiasih, Restuning; Utari, Ardhini Dwi; Jayanti, Tri Nur; Ardiyanti, Anis; Sari, Rinda Intan; Siska, Geuis Anggi (Jurnal Keperawatan Soedirman, 2019)
Background: Pregnant women are vulnerable with Anaemia. Quantitative studies related Anaemia in pregnancy have been done in Indonesia including assessing factors associated with Anaemia in pregnancy. However, none of studies provide a comprehensive view of factors that associated with anaemia in pregnancy. The aim of this review was to identify factors associated with maternal anaemia in Indonesia.Methods: The systematic scoping review method used in this review. The databases were several Indonesian electronic databases; Google scholar, Kandaga, and Sinta. The keywords were bilinguals: Indonesia and English. The inclusion criteria of studies were focused on factors related to Anaemia in pregnancy, research design included correlation and quasi-experimental, published from 2013 to 2018, full text, and Indonesian studies.Results found a total of 1986 papers were retrieved: 580 met the year criteria, and 92 articles were full text. Finally, 14 articles met the inclusion criteria and included in the analysis. Factors associated with maternal anaemia in Indonesia including health professionals’ roles, Iron tablets consumption, antenatal care, education, nutrition, health knowledge, and awareness.Conclusion and Recommendations: Multi-factors are associated with maternal anaemia in Indonesia. There is a need for comprehensive approaches from health professionals and health services in dealing with anaemia in pregnancy.